AUSTRO-HUNGARIAN ENTREPRENEURS IN RUSSIA IN THE CONDITIONS OF THE FIRST WORLD WAR - Ptitsin, Andrei Nikolaevich (Közép-Európai Közlemények, 2020)
In the presented material, a change in the situation of entrepreneurs from Austria-Hungary operating in the Russian Empire after the outbreak of the First World War is considered. They came under the influence of restrictive and liquidation measures directed against subjects of the opposing countries. As a result, part of the Austro-Hungarian enterprises in Russia was liquidated, the other reorganized with the exception of foreign owners. Only entrepreneurs of Slavic origin were able to maintain their position. They were forced to reorganize their activities to adapt to the conditions of the war. The process of liquidation of foreign entrepreneurship, which began in the war years, was subsequently brought to its logical conclusion by the Bolshevik government.